2002
DOI: 10.1034/j.1399-0004.2002.620205.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent effect of angiotensin‐converting enzyme and platelet‐activating factor acetylhydrolase gene polymorphisms on the progression of immunoglobulin A nephropathy

Abstract: In order to investigate the interdependent action of the insertion/deletion polymorphism of the angiotensin-converting enzyme (ACE) gene and polymorphism in exon 11 (C1136-->T; Ala379Val) of the platelet-activating factor acetylhydrolase (PAF-AH) gene, which encodes a functional antagonist of PAF, on the progression of immunoglobulin A (IgA) nephropathy, we analysed both polymorphisms in patients with primary IgA nephropathy, who were followed-up for longer than 3 years. During the follow-up (87.3 +/- 50.0 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In the first step, 2 studies without detailed data on the control group were excluded [25, 26]. Second, we excluded 3 studies because of the deviation from the H-W expectation [27,28,29]. Third, it was reported that PCR amplification using only flanking primer pairs would misclassify 4–5% of the ID genotype as the DD genotype [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step, 2 studies without detailed data on the control group were excluded [25, 26]. Second, we excluded 3 studies because of the deviation from the H-W expectation [27,28,29]. Third, it was reported that PCR amplification using only flanking primer pairs would misclassify 4–5% of the ID genotype as the DD genotype [17].…”
Section: Resultsmentioning
confidence: 99%
“…These findings should be viewed cautiously because many other factors, such as hypertension, are closely related to the progression of IgAN and cannot be excluded from all studies. Furthermore, whether the I/D polymorphism is just linked with other discrete loci involved in the IgAN prognosis is not clear [13, 28]. Some studies have already shown that the interaction of this polymorphism with others such as the platelet-activating factor acetylhydrolase gene C1136T polymorphism [28], ACE A2350G [37] and angiotensinogen gene M235T polymorphism [21, 25], was more important than the effect of the individual polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…When there is familial predisposition to the disease [9], the prognosis is less favorable, especially in kidney transplantation recipients [5]. Other predisposing factors include linkages to 6q22-23 and CD14/-159 polymorphism [10,11,12]. Finally, downregulation of podocyte nephrin may contribute to the development or progression of IgA nephropathy [13].…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…58 Furthermore, an IgA nephropathy study suggested that a multiple-rather than a single-gene interaction is more likely to have a significant effect on the prognosis of SLE nephritis. 57 No significant difference in angiotensinogen and angiotensin II type 1 receptor gene polymorphism on SLE was observed in a recent study. 68…”
Section: Prognostic Significance Of Ace-gene Polymorphism In Patients With Slementioning
confidence: 90%
“…In non-SLE patients, the DD-genotype was an important prognostic factor for mortality from cardiovascular 55 and renal disease. 56,57 Investigations of the possible association between SLE and an insertion/deletion polymorphism in the ACE gene have yielded contradictory results (Table 3). [58][59][60][61][62][63][64][65][66][67][68][69] This might be explained by the small sample sizes, use of population controls in some studies instead of family controls in others, ethnic heterogeneity, and different disease characteristics.…”
Section: Prognostic Significance Of Ace-gene Polymorphism In Patients With Slementioning
confidence: 99%